The NAAAA and the NCAA: Methods of Placing Legislation on the Agenda of NCAA Conventions - Schubert, George W.; Bredahl, Jeffrey A. (My University, 1987)
The authors reviewed the NCAA governance structure and process by which legislation is added to a NCAA agenda to vote. It included how legislation can be authored or sponsored by N4A.
Keywords: NCAA; legislation; governance